FOREIGN EXCHANGE MARKETS: AN ERROR CORRECTION MODEL ANALYSIS - IBM Wiyasha (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2007)
This study aims at investigating the behavior of foreign exchange rate markets in Indonesia using 1350 daily observations. Another objective of this study is to examine the structural stability due to Bali bombing chapter I and II. The markets being investigated are USD, AUD, SGD, and YEN; all relative to rupiah. The ECM is applied to investigate the behavior of the markets aforementioned. The findings of this study are that the markets are co integrated and there is a long term equilibrium relationship among them. Using the Chow test, this study finds that there is no structural stability in the markets after Bali bombing chapter I and II.